Experimental Investigation on Active Sway Control of a Gantry Crane System using PID Controller - Mohd Zaidi, Mohd Tumari; Latifah, Shabudin; Mohd Anwar, Zawawi; Mohd Razali, Daud (2013)
This project presents an experimental investigations into the development proportional integral derivative (PID) control schemes for active sway control of a gantry crane system. The main objective of controlling a gantry crane is to transport the load as fast as possible without causing any unnecessary swing at the final position. The proposed controller is used as a feedback control which is for controlling the crane position and therefore controlling the sway angle of the pendulum. Ziegler-Nichols method is used for tuning the PID in order to get the best performance of the system. The experiment was implemented on the lab-scale gantry crane pendulum system via CEM-Tools software. The PID control schemes guarantee a fast input tracking capability, precise payload positioning and very minimal sway motion. The performances of control schemes are examined in terms of sway angle reduction and time response specification.